THE ERDENETUIN-OBO PORPHYRY CU-MO MAGMA CHAMBER (MONGOLIA) AS A REFLECTION OF THE PERMIAN-TRIASSIC SUPERPLUME - Berzina A.P.; Dobretsov N.L.; Sotnikov V.I.; Ponomarchuk V.A. (My University, 2004)
Large-scale Permian-Triassic magmatism of northern and central Asia has been recently proved to be of plume origin. Based on these concepts, the present paper considers a possible relationship between the evolution of the Erdenetuin-Obo porphyry Cu-Mo magma chamber and the Siberian superplume.
Keywords: Triassic; Permian; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая; Палеозой::Пермская